IDENTIFIKASI PHYTOTELMATA YANG DIGUNAKAN SEBAGAI TEMPAT PERINDUKAN AEDES SPP. DI KEDIRI JAWA TIMUR - Fita Fitriatul Wahidah; Umi Maimunah (Jurnal Matematika dan Sains (JMS), 2021)
Phytotelmata are plants that hold water in one or more parts of their body of plant. The water that is collected in the body parts of the phytotelmata is used as a breeding habitat for Aedes spp. This study aimed to determine the diversity of phytotelamata species in Kediri, which is one of the cities with the highest DHF cases in January 2019 in East Java. This research was descriptive observational. The sampling point was determined using purposive sampling method. The results showed that there were nine species of phytotelmata which were used as breeding sites for Aedes spp. in Kediri, namely Musa paradisiaca, Colocasia esculanta, Neoregelia spectabilis, Bambusa sp., Neoregelia charm, Aechmea fasciata, Xanthosoma sagittifolium, dan Bromelia sp. Species of Aedes founded were mostly Ae. albopictus. The average volume of water contained in one part of the phytotelmata is 90.11 ml with a water temperature ranging from 25-26oC and pH of water is 6-7.